2015
DOI: 10.1037/emo0000081
|View full text |Cite
|
Sign up to set email alerts
|

Emotional competence and extrinsic emotion regulation directed toward an ostracized person.

Abstract: Positive interpersonal relationships hinge on individuals' competence in regulating others' emotions as well as their own. Nevertheless, little is known about the relationship between emotional competence and specific interpersonal behaviors. In particular, it is unclear which situations require emotional competence for extrinsic emotion regulation and whether emotionally competent individuals actually attempt to regulate others' emotions. To clarify these issues, the current investigation examined the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 62 publications
1
34
2
Order By: Relevance
“…In line with previous studies (Howard, et al, 2014;Nozaki, 2015;Riem, et al, 2013;Wesselmann, Wirth, et al, 2013), the current study showed that adolescents showed prosocial compensating behavior towards the excluded player by tossing the ball more often to that player in the compensation conditions compared to the fair play condition. Surprisingly, no differences were found in compensating behavior towards ingroup versus outgroup members.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies (Howard, et al, 2014;Nozaki, 2015;Riem, et al, 2013;Wesselmann, Wirth, et al, 2013), the current study showed that adolescents showed prosocial compensating behavior towards the excluded player by tossing the ball more often to that player in the compensation conditions compared to the fair play condition. Surprisingly, no differences were found in compensating behavior towards ingroup versus outgroup members.…”
Section: Discussionsupporting
confidence: 92%
“…They are also useful to accurately predict external variables. In fact, previous studies found that intrapersonal and interpersonal EC were differently related to external criteria—for example, intrapersonal EC was more strongly related to objective indices of health [30], depression [33] and regulation of one’s own emotions [36, 72], whereas interpersonal EC was more strongly related to behaviors aimed at regulating others’ negative emotions [7, 73]. These results suggest that intrapersonal versus interpersonal dimensions can afford more nuanced exploration of relationships between EC and external variables and increase its predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research has found that it had an adequate reliability and incremental validity over the Big Five personality traits [6, 28]. Given its strengths, the PEC has been rapidly adopted in recent EC research [5, 7, 3037].…”
Section: Introductionmentioning
confidence: 99%
“…T he expression of emotional intelligence (EI) in professional activities and sports has been of interest to many researchers (Clark, 2016;Kopp & Jekauc, 2018;Laborde, Dosseville, & Allen, 2015;Magrum et al, 2019;Nozaki, 2015;Pursun & Efilti, 2019;Ubago-Jiménez, González-Valero, Puerto-Molero, & Garcia-Martínez, 2019). It has been revealed (Kaup & Jekauc, 2018) that EI has a positive effect on athletes' performance and may also be related to stress management or the athletes' own motivation to play sport (Ubago-Jiménezet al, 2019).…”
Section: Introductionmentioning
confidence: 99%